Exact Propagators for Soliton Potentials - Pupasov, A.M.; Samsonov, B.F. (Symmetry, Integrability and Geometry: Methods and Applications, 2005)
Using the method of Darboux transformations (or equivalently, supersymmetric quantum mechanics), we obtain an explicit expression for the propagator for the one-dimensional Schrödinger equation with a multi-soliton potential.